Evaluate each of the following using identities:$(2x -\frac{1}{x})^2$


Given:

$(2x -\frac{1}{2}x)^2$

To do:

We have to evaluate the given expression using a suitable identity.

Solution:

We know that,

$(a+b)^2=a^2+b^2+2ab$

$(a-b)^2=a^2+b^2-2ab$

$(a+b)(a-b)=a^2-b^2$
Therefore,

$(2 x-\frac{1}{x})^{2}=(2 x)^{2}+(\frac{1}{x})^{2}-2 \times 2 x \times \frac{1}{x}$

$=4 x^{2}-4+\frac{1}{x^{2}}$

Hence, $(2 x-\frac{1}{x})^{2}=4 x^{2}-4+\frac{1}{x^{2}}$.

Tutorialspoint
Tutorialspoint

Simply Easy Learning

Updated on: 10-Oct-2022

13 Views

Kickstart Your Career

Get certified by completing the course

Get Started
Advertisements